(Un)making the grade: An instructor’s guide to mitigating the negative impacts of grades within a neoliberal university system - Brook, Adriana (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2022)
Critics of the neoliberal university argue that grading undermines student learning. In this article, I survey the literature in order to ascertain whether such critiques are supported by pedagogical research. Investigating the relationship between grading and motivation, feedback, and autonomy, respectively, I conclude that grades most often do undercut learning. I explore the implications for instructors at Canadian universities, suggesting that abandoning grades is currently neither feasible nor best for students. I propose pragmatic adaptations to common grading practices that better promote learning and conclude that the implementation of less grade-centric assessment strategies is not only the best way to support student learning but also a way to challenge and mitigate the influences of neoliberal ideology in higher education.